Analysis of Heat Strain on Production Workers Due to Exposure to Hot Working Climate at CV. X - Moch. Sahri; Ratna Ayu Ratriwardhani; Friska Ayu; Siti Arrum Julia Azzahra Giri (Preventif : Jurnal Kesehatan Masyarakat, 2026)
A hot work climate is one of the risk factors that can negatively affect occupational health and safety, especially in production industries that use fiberglass materials, such as CV. X. A work environment with temperatures exceeding the threshold limit value (TLV) has the potential to cause heat strain complaints, which can reduce productivity and increase the risk of health problems among workers. This study aims to analyze the level of heat strain among production workers due to exposure to a hot work climate. This research uses a descriptive quantitative method with a cross-sectional design and total sampling involving 10 production workers. Data were obtained through measurements of the Wet Bulb Globe Temperature (WBGT) index in the production area using the Heat Stress Apparatus Quest Temp 46, as well as the assessment of heat strain using the Physiological Strain Index (PSI) based on workers’ body temperature and pulse rate before and during work. The results showed that the WBGT value in the production area, with an area of 288 m², was 30.1°C, exceeding the TLV for a moderate workload category (28°C). Individual characteristics such as age, nutritional status, and water intake were obtained through interviews using questionnaires.